Datura stramonium – A Dangerous Weed and Alternative Drug of Abuse: An Overview of Poisoning Cases in 21st Century - Aćimović, Milica (Planta Medica, 2025)
Datura stramonium is a well-known cosmopolitan weed known by several common names: thorn apple (due to the appearance of its fruits), Angelʼs trumpet (linked to its flowers), loco seed (referring to the hallucinogenic properties of its seeds), jimson weed (originating from the first recorded poisoning involving this plant), and apple of Peru (indicating the plantʼs origin). All parts of the plant contain the tropane alkaloids hyoscyamine, scopolamine, and atropine together with several minor alkaloids, which cause poisoning such as typical anticholinergic syndrome with neuropsychiatric effects. A review of 114 papers from various databases (Scopus, Web of Science, PubMed, and Google Scholar) revealed that poisoning incidents involving this plant have been relatively common from 2001 to 2024. The analysis indicated that all cases of poisoning from D. stramonium can be categorized into two main groups: accidental and misuse. Accidental poisonings are primarily linked to the contamination of other crops in the field, leading to mass poisoning of humans and animals. They can also result from misidentifying the plant as another edible species, childrenʼs curiosity, and self-medication. On the other hand, misuse is typically associated with recreational drug use, suicide attempts, criminal activities, and magico-religious practices. To prevent poisoning from this plant, it is essential to eliminate the weed from fields, yards, gardens, and other disturbed areas. Additionally, it is important to educate the general public about the plantʼs appearance and the dangers associated with its consumption, particularly in the context of self-medication and recreational drug use.
Keywords: accidental poisoning; Datura stramonium; misuse; Solanaceae; tropane alkaloids